Pengaruh Beban Kerja dan Lingkungan Kerja Fisik terhadap Kinerja Karyawan PT Inoac Polytechno Indonesia di Karawang Jawa Barat - Riyanto, Tantira Zalianti; Ariyanti, Eti (SCIENTIFIC JOURNAL OF REFLECTION : Economic, Accounting, Management and Business, 2025)
In the context of industrial growth and increasing performance demands, employee productivity has become a crucial focus for organizational success. PT Inoac Polytechno Indonesia, located in Karawang, West Java, faces challenges related to optimizing employee performance amidst varying workloads and physical work environment conditions. This study aims to examine the influence of workload and physical work environment on employee performance. The research employed a causal associative method with a quantitative approach. The population consisted of 80 employees, with total sampling (saturated sampling) used as the sampling technique. Data were collected through questionnaires and analyzed using validity and reliability tests, classical assumption tests, linear regression analysis, correlation coefficient analysis, coefficient of determination, and hypothesis testing. The findings reveal that both workload and physical work environment have a significant influence on employee performance, both partially and simultaneously. A well-managed workload positively impacts productivity, while a supportive physical work environment enhances work efficiency. When these two factors are optimized together, their combined influence significantly strengthens employee performance. The implications of this study emphasize the importance of managerial strategies in balancing workload distribution and maintaining a conducive work environment to enhance overall employee well-being and performance in the long term.